Pemenuhan Hak Atas Pekerjaan Bagi Mantan Narapidana Di Kabupaten Purworejo - Arih Filian Prabowo (Faculty of Law Universitas Islam Indonesia, 2022)
Provisions regarding the use of Police Record Certificates have become an obstacle for former convicts to enter the job market. Therefore, two formulations of the problem were identified, namely first, How is the fulfillment of the right to work for former convicts in Purworejo Regency? Second, what are the supporting and inhibiting factors in fulfilling the right to work for former convicts in Purworejo Regency? This is an empirical legal research with statutory and conceptual approaches. The results of this study conclude that first, the Police Record Certificate is an obstacle in securing a job for former convicts in Purworejo Regency; and secondly, there have been efforts undertaken by the regional government of Purworejo district in assisting in fulfilling the right to work for former convicts in Purworejo RegencyKey Word: The right to work, Former convicts, Government of Purworejo Regency AbstrakKetentuan mengenai pemakaian Surat Keterangan Catatan Kepolisian menjadi penghambat mantan narapida untuk mencari pekerjaan. Oleh karena itu, diidentifikasi dua rumusan masalah, yaitu pertama, Bagaimana pemenuhan hak atas pekerjaan bagi mantan narapidana yang di Kabupaten Purworejo? Kedua, Apa faktor penunjang dan penghambat dalam pemenuhan hak atas pekerjaan bagi para mantan narapidana di Kabupaten Purworejo? Jenis penelitian merupakan penelitian hukum empiris dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian ini menyimpulkan pertama, Surat Keterangan Catatan Kepolisian menjadi penghambat dalam mencari pekerjaan di Kabupaten Purworejo; dan kedua, upaya oleh pemerintah daerah kabupaten Purworejo dalam membantu dalam memenuhi hak atas pekerjaan bagi mantan narapidana di Kabupaten Purworejo.Kata-kata Kunci: Hak atas pekerjaan, Mantan narapidana, Pemerintah Kabupaten Purworejo